Kim Jiyoung, born 1982, and the labour market: Overeducation, gender, income and life satisfaction. Panel evidence from Korea - Amina Ahmed Lahsen; Alan T. Piper; Ida-Anna Thiele (Freie Universität Berlin, School of Business & Economics, 2020)
One reason often put forward for South Korea's rapid economic growth has been the rising level of educational attainment of its workforce. Correspondingly, the proportion of Koreans who complete tertiary education has also rapidly increased (and is also considerably higher than the OECD average). Such increases raise the possibility of overeducation if the amount of jobs which require such education do not increase at a similar pace. Among the consequences of overeducation are reduced life satisfaction and underutilised human capital. Given that Korean females are better educated than males, and they also face more discrimination in the labour market, the consequences of overeducation are likely to differ by gender. Using Korean panel data and both a subjective and objective measure of overeducation, the results are consistent with females having lower aspirations despite their high levels of education, and indicate that a more female friendly labour market could address the country's currently underutilised human capital, for the benefit of the females themselves, as well as males, and the Korean economy.
urn:nbn:de:kobv:188-refubium-27553-5
Keywords: 330; overeducation; gender; gender inequality; incomelife satisfaction; Korea